Influence of exponential space-based heat source and Joule heating on nanofluid flow over an elongating/shrinking sheet with an inclined magnetic field. Issue 1 (31st December 2022) - Swain, Kharabela; Animasaun, Isaac Lare; Ibrahim, S. Mohammed
ABSTRACT: One thing that is not yet knows is the effect of increasing space-dependent internal heat source on the dynamics of recyclable iron oxide-supported copper oxide nanocatalyst in the industry. This study presents not only the effect of exponential space-dependent heat source (ESHS) and Joule heating on such dynamics using the nanofluid model but also the impact of magnetic strength proportional to Lorentz force. The dimensional governing equations, suitable to model the boundary layer flow of water conveying Cu and CuO nanoparticles through the porous medium on a convectively heated surface, were modelled using the Darcy model. Similarity solution of the problem was obtained using the suitable similarity solution. Numerical solution of the corresponding boundary value problem was sought for using MATLAB-based bvp4c package. Magnetic parameter declines the motion of the nanofluids (water conveying copper nanoparticles and water conveying cupric nanoparticles) but accelerates the temperature profile.